2008
DOI: 10.2174/138161208784007699
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase Inhibitors: New Hope for Rheumatoid Arthritis?

Abstract: Histone deacetylase (HDAC) inhibitors are a new family of anti-cancer agents currently undergoing clinical investigations for various oncology indications. Their anti-inflammatory activities had been well documented and they appear to be potential therapeutic strategies for various inflammatory diseases. In this review, the anti-inflammatory activities of HDAC inhibitors with emphasis on their potential applications in rheumatoid arthritis (RA) will be summarized. The possible anti-rheumatic mechanisms, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 175 publications
(358 reference statements)
1
41
0
1
Order By: Relevance
“…[21][22][23][24] Recently evidence has indicated that lignans from Schisandra chinensis have the capacity to suppress the inflammatory response induced by bacterial components such as LPS. 19,25,26) Guo et al (2008) reported that schisandrin inhibited NO production, prostaglandin E 2 release, COX-2, and inducible nitric oxide synthase expression, and that these effects were due to inhibition of NF-B, JNK, and p38 MAPK activities in a Raw 264.7 macrophage cell line. 19) These results are in agreement with ours, because gomisin J, gomisin N, and schisandrin C are also Schisandra chinensis Bail derived lignans, and they inhibited NO production by Raw 264.7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23][24] Recently evidence has indicated that lignans from Schisandra chinensis have the capacity to suppress the inflammatory response induced by bacterial components such as LPS. 19,25,26) Guo et al (2008) reported that schisandrin inhibited NO production, prostaglandin E 2 release, COX-2, and inducible nitric oxide synthase expression, and that these effects were due to inhibition of NF-B, JNK, and p38 MAPK activities in a Raw 264.7 macrophage cell line. 19) These results are in agreement with ours, because gomisin J, gomisin N, and schisandrin C are also Schisandra chinensis Bail derived lignans, and they inhibited NO production by Raw 264.7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…86 HDACis suppress proinflammatory cytokine release in cultured PBMCs, macrophages, T cells and epithelial cells [87][88][89][90][91][92][93][94][95] and suppress inflammation in animal models of concanavalin-A-induced hepatitis 92 and lipopolysaccharideinduced endotoxemia. 89,91 HDACis have received significant attention as novel agents for rheumatoid arthritis, 96 capable of reducing inflammation, synovial fibroblast proliferation, joint swelling and bone and cartilage destruction in rodent models of rheumatoid arthritis. [97][98][99][100][101][102] Preclinical efficacy has also been observed in models of inflammatory bowel disease 95,103,104 and central nervous system inflammation.…”
Section: Antiinflammatory Effects Of Hdacismentioning
confidence: 99%
“…Modulation of these enzymes using HDAC inhibitors (HDACi) is emerging as a promising treatment not only for cancer [1][2][3] but also for neurodegenerative diseases, asthma, rheumatoid arthritis, viral infections and malaria [4][5][6][7][8][9][10][11]. A number of HDACi have progressed to the clinic, or are in clinical trials, for treating solid and haematological tumours [1][2][3].…”
Section: Introductionmentioning
confidence: 99%